Design and biocompatibility of endovascular aneurysm filling devices. Issue 4 (4th August 2014) - Rodriguez, Jennifer N.; Hwang, Wonjun; Horn, John; Landsman, Todd L.; Boyle, Anthony; Wierzbicki, Mark A.; Hasan, Sayyeda M.; Follmer, Douglas; Bryant, Jesse; Small, Ward; Maitland, Duncan J.
Abstract The rupture of an intracranial aneurysm, which can result in severe mental disabilities or death, affects approximately 30, 000 people in the United States annually. The traditional surgical method of treating these arterial malformations involves a full craniotomy procedure, wherein a clip is placed around the aneurysm neck. In recent decades, research and device development have focused on new endovascular treatment methods to occlude the aneurysm void space. These methods, some of which are currently in clinical use, utilize metal, polymeric, or hybrid devices delivered via catheter to the aneurysm site. In this review, we present several such devices, including those that have been approved for clinical use, and some that are currently in development. We present several design requirements for a successful aneurysm filling device and discuss the success or failure of current and past technologies. We also present novel polymeric‐based aneurysm filling methods that are currently being tested in animal models that could result in superior healing. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A 103A: 1577–1594, 2015.